1984
DOI: 10.1002/jcp.1041190305
|View full text |Cite
|
Sign up to set email alerts
|

Rb+ influx in response to changes in energy generation: Effect of the regulation of the ATP content of HELa cells

Abstract: The effect of changes in energy metabolism on Rb+ influx was studied in HeLa cells. Irrespective of whether ATP production was controlled by varying the activity of glycolysis or of oxidative metabolism on addition of certain combinations of glucose, carbonylcyanide m-chlorophenylhydrazone, monoiodoacetic acid, and quercetin, Rb+ influx changed as a linear function of the ATP content, which varied in a wide range up to the normal level (15-20 nmol/mg protein or 3-4 mM). The difference between results obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 31 publications
(30 reference statements)
2
9
0
Order By: Relevance
“…It may be speculated that ATP concentration in MDCK cells, but not in HEK, is limiting for Na-K-ATPase activity, in keeping with the previously demonstrated effect of adducin that increases Na-K-ATPase activity by enhancing the affinity for ATP (11). This may be supported by studies in HeLa and intact renal tubular cells, where pump activity changes as linear function of the ATP content (20,40). As opposed to MDCK cells, HEK exhibit high K influx per site, but it is well known that HEK are very different from MDCK, as they are not polarized and do not form tight junctions (44).…”
Section: Discussionsupporting
confidence: 66%
“…It may be speculated that ATP concentration in MDCK cells, but not in HEK, is limiting for Na-K-ATPase activity, in keeping with the previously demonstrated effect of adducin that increases Na-K-ATPase activity by enhancing the affinity for ATP (11). This may be supported by studies in HeLa and intact renal tubular cells, where pump activity changes as linear function of the ATP content (20,40). As opposed to MDCK cells, HEK exhibit high K influx per site, but it is well known that HEK are very different from MDCK, as they are not polarized and do not form tight junctions (44).…”
Section: Discussionsupporting
confidence: 66%
“…The differences between the results obtained using broken membrane fragments and intact tubules may have been due to differ ences between the constituents of the ATPase hydrolytic assay medium and the intracellular milieu of the proximal tubule, including ADP, Pi> magnesium, and other cellular factors known to alter Na,K-ATPase activity. In a different study, a linear dependence of rubidium (potassium) transport on the A TP content was observed using HeLa cells, a nonepithelial preparation, and there was no difference in the linear relationship whether the A TP was produced by aerobic glycolysis or oxidative phosphorylation (47). These results, along with those in the kidney, suggest that at least under some conditions transport activity may be directly dependent on the concentration of ATP.…”
Section: Quantitative Relationship Between Active Transport and Atpmentioning
confidence: 63%
“…However, several studies have shown that in isolated cells from various sources, the rates of ouabain-sensitive K + (or S6Rb) transport increase linearly with a rise in [ATP] to 8-10 mM (Ikehara et al, 1984;Soltoff and Mandel, 1984;Tessitore et al, 1986). If this were true for the CNS cells as well, one could surmise that the neuronal Na pump in vivo may not operate at its maximal capacity.…”
Section: Discussionmentioning
confidence: 99%